The Interaction of User Experiences with Digital Economy Platforms and Creative Writing: Empirical Evidence from Indonesia - Sari, Retno Purwani (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The current study investigates how Indonesian user experiences with digital economy platforms support creative writing as a marketing communication strategy. This study employed a cross-sectional qualitative research design. At a single point in time, data on the assumptions of research participants were collected using questionnaires. To assess what and how participants shared their experiences and assumptions, interaction analysis was used. Preliminary findings indicate that Indonesian user experiences with digital economy platforms have an impact on the quality and accuracy of their writing. The findings revealed that digital writing principles – language choices, writing styles, and engagement with popular culture – are present in today’s creative writing. This implies that a minor change in the marketing message completely alters how and where it is promoted. Creative writing skills and digital literacy are valued in the labor market. These results are useful as a basis for strategic planning in the Indonesian educational system and marketing communication.